Goal Setting and Strategies to Enhance Goal Pursuit for Adults With Acquired Disability Participating in Rehabilitation - Levack, WM; Weatherall, M; Hay-Smith, EJ; Dean, SG; McPherson, KM; Siegert, RJ (John Wiley & Sons, Inc., 2015)
Goal setting is considered a key component of rehabilitation for adults with acquired disability, yet there is little consensus regarding the best strategies for undertaking goal setting and in which clinical contexts. It has also been unclear what effect, if any, goal setting has on health outcomes after rehabilitation.